Corrigendum and Addendum: Abstract M- and Abstract L-Spaces of Polynomials on Banach Lattices. Issue 4 (6th January 2017) - Bu, Qingying; Buskes, Gerard; Li, Yongjin
Abstract: In this short note, we correct and reformulate Theorem 3.1 in the paper published in Proceedings of the Edinburgh Mathematical Society 58 (3) (2015), 617–629.